2017
DOI: 10.1159/000479789
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Ginger (<b><i>Zingiber officinale</i></b> Roscoe) Extract against Oxidative Stress and Mitochondrial Apoptosis Induced by Interleukin-1β in Cultured Chondrocytes

Abstract: Aims: The protective effects of ginger (Zingiber officinale Roscoe) extract on IL-1β-mediated oxidative stress and mitochondrial apoptosis were investigated in C28I2 human chondrocytes. Methods: The effects of various concentrations of ginger extract on C28I2 human chondrocyte viability were evaluated in order to obtain noncytotoxic concentrations of the drug by methylthiotetrazole assay. The cells were pretreated with 5 and 25 μg/mL ginger extract for 24 h, followed by incubation with IL-1β (10 ng/mL) for 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(44 citation statements)
references
References 46 publications
4
40
0
Order By: Relevance
“…In a study by Hosseinzadeh and co-workers (2017), the toxicity of ginger on chondrocytes was investigated, and no cytotoxicity was observed even at high concentrations of ginger extract in chondrocyte cells [69]. In addition, they reported that ginger extract could significantly reduce IL-1β-induced oxidative stress, mitochondrial changes, and apoptosis [69].…”
Section: Gingermentioning
confidence: 99%
“…In a study by Hosseinzadeh and co-workers (2017), the toxicity of ginger on chondrocytes was investigated, and no cytotoxicity was observed even at high concentrations of ginger extract in chondrocyte cells [69]. In addition, they reported that ginger extract could significantly reduce IL-1β-induced oxidative stress, mitochondrial changes, and apoptosis [69].…”
Section: Gingermentioning
confidence: 99%
“…Zingiber officinale is a rhizome commonly consumed as a delicacy, medicine or spice [10] Ginger is a strong antioxidant substance and may either mitigate or prevent generation of free radicals. It has been reported for antioxidants and protective role against toxicants, insecticidal, antimicrobial and antiprotozoal activities [11][12][13][14]. It has also been recently been reported to improve growth performances in experimental animals [15].…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by the presence of essential oil and a mixture of pungent tasting phenolic compounds (gingerols, gingerdiols, gingerdiones, dihydrogingerdiones, and shogaols) [7]. In a recent in vitro study, it has been shown that ginger extract was able to attenuate oxidative stress and reduce succeeding cell death of chondrocytes resulting from a mitochondrial apoptosis [56]. Ginger preparations also inhibited LPS-induced PGE 2 formation in U937 cells and decreased levels of TNF-α and IL-1β in murine peritoneal macrophages [57].…”
Section: Herbal Medicinal Products For Oral Use In the Treatment Of Omentioning
confidence: 99%